Report on proposed new interior design of spice of India restaurant for Spice Global at No. 36 Lorong Cheah Cheng Lim Off Jalan Di-Hilir 30350 Perak Darul Ridzuan / Noorsyahidah Jaafar - Jaafar, Noorsyahidah (2010)
Final project of Diploma Interior Design is base on student understanding about the interior design project in wide scope from to find project proposal, find the client, find the site for the project to the design development process.The selected final project for my final semester is a Proposed New Interior Design Spice Of India Restaurant For Spice Global at No.36 Lorong Cheah Cheng Lim Off Jalan Di-Hilir, 30350 Ipoh, Perak Darul Ridzuan Spice of India Restaurant was incorporated in 2003,its core business activities lie in operating Indian restaurants. The company's long term strategic objective is to capture the fine dining market. The concept and image is also applied with Indian style through the interior and exterior to appeal the restaurant will be able to lure more tourists and visitors to come. There were several researches done to succeed this Spice of India Restaurant amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the Spice of India Restaurant demands in terms of achieve the objectives.